2005
DOI: 10.1136/sti.2004.012047
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of human papillomavirus self testing in female adolescents

Abstract: Objectives: To develop scales assessing acceptability of human papillomavirus (HPV) testing in adolescents, to compare acceptability of self to clinician testing, and to identify adolescent characteristics associated with acceptability. Methods: Female adolescents 14-21 years of age attending a hospital based teen health centre self collected vaginal samples and a clinician, using a speculum, collected cervicovaginal samples for HPV DNA. Acceptability of and preferences for self and clinician testing were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 39 publications
3
64
0
1
Order By: Relevance
“…This result is not surprising, given that most women know and accept the Pap smear as an effective method for cervical screening despite the side effects of discomfort and embarrassment [3,6,27]. In this respect, selfsampling for HPV is a less painful and embarrassing procedure than the Pap test.…”
Section: Discussionmentioning
confidence: 81%
“…This result is not surprising, given that most women know and accept the Pap smear as an effective method for cervical screening despite the side effects of discomfort and embarrassment [3,6,27]. In this respect, selfsampling for HPV is a less painful and embarrassing procedure than the Pap test.…”
Section: Discussionmentioning
confidence: 81%
“…High satisfaction with self-sampling in supervised settings has also been reported by most of the previous studies (10,18,33,39). Yet, some report preference for physician collection of samples (16,19) and, in a study done in China, rural women preferred to do selfsampling at the clinic rather than at home (28). Further study is required to identify factors affecting satisfaction with home or unsupervised self-sampling for HPV and to identify populations more likely to benefit from this sampling method.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that self-sampling under optimal conditions in clinical or supervised settings is both accurate (8)(9)(10)(11)(12)(13)(14)(15) and preferred by patients (16)(17)(18)(19). In a recent systematic review, the sensitivity and specificity of self-sampling for identifying high-risk HPV were 74% and 88% compared with physician sampling (12).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported that self-collection of vaginal samples was not preferred over collection by health care workers (7-10) but was acceptable. The reasons for not preferring self-collection of vaginal samples have included concerns about collecting an inadequate sample (10-13) and that self-collection was not as comfortable as collection by health care workers (12).…”
mentioning
confidence: 99%